Baromfitrágya alapú komposzt szuszpenzió hatásának vizsgálata káposzta (Brassica oleracea L. convar. capitata provar. capitata Dutch) tesztnövénnyel - Gorliczay, Edit; Kiss, Nikolett Éva; Nagy, Attila; Tamás, János (GEORGIKON FOR AGRICULTURE, 2022)
Compost teas are watery extracts of composted materials that are used to control plant diseases and on crop fertilization. In this work, we tested the nutrient replenishment effect of a broiler and hen manure-based non-aerated compost tea on two soil types (Arenosol, slightly humous Arenosol), with cabbage (Brassica oleracea L. convar. capitata provar. capitata Dutch) as a test plant, at one water capacity level (Field Capacity 70 w/w%), with harvesting times of four and eight weeks. The trends in leaf number, wet weight (g), total length (cm), Fv/Fm, Fv/Fo, total chlorophyll (μg/g) and total carotenoids (μg/g) were investigated. Based on the results of the pot experiments, significant differences (p
Keywords: poultry manure; cabbage; pot experiment; compost tea